SISTEM INFORMASI PENJUALAN PAKAIAN BERBASIS WEB PADA TARGET FACTORY OUTLET - Albert Albert; Dali Santun Naga; Ery Dewayani (Jurnal Ilmu Komputer dan Sistem Informasi, 2020)
Website “Sistem Informasi Penjualan Pakaian Berbasis Web Pada Target Factory Outlet” aimed at helping Target Factory Outlet to expand market share and increase the credibility of Target Factory Outlet itself. The results obtained are websites with the domain name ‘targetfo.store’ which have been hosted can be accessed by website visitors. The making of the website uses System Development Life Cycle (SDLC) method which is carried out in several phases namely analysis, design, implementation, installation, testing, and maintenance. This website uses several design tools, namely Flowchart, Data Flow Diagram, Entity Relationship Diagram, Context Diagram and Relationship Between Tables. Testing this website uses Black Box Testing and User Acceptance Test(UAT) method. This website is created using HTML and PHP programming languages and uses MySQL as a Database Management Software (DBMS). The website ‘targetfo.store’ has the advantage of having goods import reports, sales reports and financial reports that can be seen by Target Factory Outlet owner.